2011
DOI: 10.4049/jimmunol.1001824
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Regulation of the Mucosal Immune Complexity in the Basal Chordate Amphioxus

Abstract: Both amphioxus and the sea urchin encode a complex innate immune gene repertoire in their genomes, but the composition and mechanisms of their innate immune systems, as well as the fundamental differences between two systems, remain largely unexplored. In this study, we dissect the mucosal immune complexity of amphioxus into different evolutionary-functional modes and regulatory patterns by integrating information from phylogenetic inferences, genome-wide digital expression profiles, time course expression dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 54 publications
5
39
0
Order By: Relevance
“…However, there was no evidence of a response when TLR ligands and PAMPs were used to stimulate CgTLR transfected cells. The lack of PAMPs recognition was consistent with previous reports for amphioxus and Drosophila [6,29]. In contrast, Sasaki et al demonstrated that ascidian Cionaintestinalis TLRs show low level responses to high concentrations of PAMPs [30], however, such a response is too weak to distinguish from C. intestinalis TLR's authentic ability and the background response of cell line.…”
Section: Discussionsupporting
confidence: 79%
“…However, there was no evidence of a response when TLR ligands and PAMPs were used to stimulate CgTLR transfected cells. The lack of PAMPs recognition was consistent with previous reports for amphioxus and Drosophila [6,29]. In contrast, Sasaki et al demonstrated that ascidian Cionaintestinalis TLRs show low level responses to high concentrations of PAMPs [30], however, such a response is too weak to distinguish from C. intestinalis TLR's authentic ability and the background response of cell line.…”
Section: Discussionsupporting
confidence: 79%
“…Initially, we obtained the gene-expression profile after bacterial challenge by sequencing differentially expressed genes using the suppression subtractive hybridization method (46) and then by sequencing the cDNA library of amphioxus in response to early antibacterial infection via 454 Sequencing (38). Through these approaches, extensive immune-related genes were identified in amphioxus, but no miRNAs were found to be involved in regulation of the immune system.…”
Section: Difference In Mirna Response Between Amphioxus and Vertebratmentioning
confidence: 99%
“…They are representatives of Gram-positive (G+) and Gram-negative (G2) bacteria, respectively. Four amphioxus acute-phase response genes, including Complement component C3 (AB050668), Dermatopontin (EB677005), Peptidoglycan recognition protein S1 precursor (EB676974), and Rhamnose-binding lectin precursor (AY616196), were selected to detect the immune activation based on our pre- vious study (38,46). Under both S. aureus and V. anguillarum challenge, the expression of the four amphioxus genes rose quickly and achieved a steady-state level at ∼24 h (Fig.…”
Section: Acute-phase Mirna Response In Amphioxus Upon Bacterial Challmentioning
confidence: 99%
See 2 more Smart Citations